Sustainable Finance for Independent Palm-Oil Smallholders in Sabah - Jessita Joseph; Mohd Afifi Bin Mohd Nasir (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2026)
Malaysia is the second largest palm oil producer in the world after Indonesia, while Sabah is a major contributor to Malaysia’s palm oil production with over 50,000 smallholders that plays an important role in economic development. However, the demand for sustainable palm oil, driven by deforestation and human rights, has led to stringent requirements, for instance, Malaysian Sustainable Palm Oil (MSPO) and Roundtable on Sustainable Palm Oil (RSPO). The upcoming EU Deforestation Regulation (EUDR) further intensifies this pressure, which demanding palm oil industry’s traceability and transparency of supply chain and deforestation-free commodities. While Sabah pledged to achieve 100% fully certified by 2025, significant challenges remain; most independent smallholders are still uncertified, with only 885 total certified as of 2023, which is only 3% from the total 30,000 smallholders. This qualitative study is based on a secondary data review, which identifies key barriers faced by independent smallholders to comply with the certification requirement. High certification cost, less training, land title issues, and uncertainty of premiums are among the identified challenges. Existing initiatives are reviewed and found to have insufficient initiative taken to overcome these hurdles. The study concluded that without tailored intervention, these independent smallholders risk exclusion from the EU market. To address this, the study proposes actionable, multistakeholder recommendations that include cooperative models for group certification, expanding training programs, leveraging technology, and resolving legal issues. The findings underscore that achieving this sustainability and EU Deforestation Regulation (EUDT) compliance requires inclusive strategies that make certification more attractive but economically reasonable and practical among independent smallholders.